E-Money As A Payment System Tool In Flazz Bca Card Users In Surabaya - Rizqi, Muhaimin Nur; Ady, Sri Utami (Universitas Dr. Soetomo, 2019)
The purpose of this research is to understand and analyze to find out the e-money wisdom in Indonesia as a new payment system tool for users of BCA Flazz cards. This research uses Purposive Sampling techniques, namely the method of determining the sample with specific considerations